A techno-economic sizing method for grid-connected household photovoltaic battery systems. (1st July 2020) - Zhang, Yijie; Ma, Tao; Elia Campana, Pietro; Yamaguchi, Yohei; Dai, Yanjun
Highlights: Grid-connected photovoltaic battery systems are simulated under dynamic electricity tariffs. Reference sizing combinations are obtained via system techno-economic analysis. High self-sufficiency leads to more schedulable production, sold energy and less battery usage. Subsidies impact the revenues obviously especially in high self-sufficiency cases. Partial grid parity could be achieved under the current market conditions. Abstract: Battery storage provides an effective solution to alleviate the burden of the intermittent photovoltaic production on the grid and increase photovoltaic penetration in residential houses. Despite several existing work dedicated to the evaluation of photovoltaic battery system, the research on system sizing and operation strategy of the household system still has substantial areas to be explored such as techno-economic analysis under different electricity tariffs and comprehensive parametric analyses. In this paper, the mathematical model of a photovoltaic battery system is developed to investigate system performance, based on the various economic and technical indicators. This study demonstrates that the integration of battery energy storage could increase the value of self-consumption and self-sufficiency rates while making payback period longer. Substantial photovoltaic battery systems have been simulated under practical dynamic electricity tariffs in a typical electricity market. Eight cases with different technical performances from the recommended reference combinations are compared and studied in detail. The energy flows among photovoltaic, battery bank, grid and household user are discussed, revealing that systems with high self-sufficiency rate lead to more schedulable photovoltaic production, sold electricity and lower battery usage rate than those with high self-consumption rate. Besides, the entire lifecycle economic analysis indicates that a higher self-sufficiency rate refers to higher initial investment but shorter payback period and larger profit. The revenues breakdown of the cases shows that subsidies have a significant impact, especially for cases with high self-sufficiency rate. The levelized cost of electricity of photovoltaic and photovoltaic battery systems ranges from 0.373 to 0.628 CNY/kWh, demonstrating the possibility of partial grid parity under the current situation in Shanghai.